Buchwalter-Schmets theorems and linear topologies - L. M. Sánchez Ruiz; J. R. Ferrer (International Journal of Mathematics and Mathematical Sciences, 1999)
In this paper, we obtain Buchwalter-Schmets theorems in the realm of Lefschetz linearly topologized spaces.